2020
DOI: 10.1111/eje.12570
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship availability and needs for junior faculty members at the United States and Australian dental schools

Abstract: Upon entering a career in dental education, the novice academic is expected to successfully navigate an often unfamiliar environment of teaching, scholarly activity and research, as well as perform administrative tasks and participate in both university and community service. 1 The job demands and pressures placed on modern day dental educators continue to diversify and expand due to advancements in educational technology, evolving dental curricula, and changes in healthcare delivery systems. 1-4 With little t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Higher education institutions cannot ignore these transformational drivers of change in dental education. Upon entering a career in academia, there is the expectation that novice academics can meet the increasing demands of teaching, scholarly activity, and research; perform administrative tasks; and participate in both university and community services [ 7 ]. Oral and dental care play an important role in the health and well-being of the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher education institutions cannot ignore these transformational drivers of change in dental education. Upon entering a career in academia, there is the expectation that novice academics can meet the increasing demands of teaching, scholarly activity, and research; perform administrative tasks; and participate in both university and community services [ 7 ]. Oral and dental care play an important role in the health and well-being of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring was first developed in the United States of America in the 1970s within large corporations to support junior staff [1] but has now extended to other contexts, including the university-based education platforms of health professionals [2][3][4][5][6][7][8][9][10][11][12][13]. Over the years, the reforms in the education of health professionals have contributed to the doubling of life expectancy during the 20th century [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The breakdown of dentists registered with the Health Professions Council of South Africa (HPCSA) for 2015, according to age, gender and race, showed that younger dentists were predominantly female and Black while older dentists were mainly White and male. 14 To empower the academic staff with the necessary pedagogical skills, 9 the recommendation of the American Dental Education Association about mentoring [16][17][18][19][20] becomes relevant to the RSA. Descriptions about mentorship "encompass a synergistic relationship between a mentor with accumulated expertise and a mentee with novice-like inexperience, who engage in the sharing of knowledge and personal experiences to facilitate career development and guidance towards a path of promotion, fulfilment and overall success ...a lack of mentorship may result in failure to retain junior faculty at an institution or within academia altogether."…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions about mentorship "encompass a synergistic relationship between a mentor with accumulated expertise and a mentee with novice-like inexperience, who engage in the sharing of knowledge and personal experiences to facilitate career development and guidance towards a path of promotion, fulfilment and overall success ...a lack of mentorship may result in failure to retain junior faculty at an institution or within academia altogether." [p2] 18 In 2019, there were approximately 100 academics within the faculty, required to teach and provide dental care services in hospitals and communities. 21 The profile of the academics reflected the general profile of those reistered with the HPCSA.…”
Section: Introductionmentioning
confidence: 99%